2008
DOI: 10.1007/s00502-008-0525-0
|View full text |Cite
|
Sign up to set email alerts
|

A bulk acoustic wave(BAW)-based sensor node for automotive wireless sensor networks

Abstract: The following paper presents a 2.1 GHz transceiver, which makes use of BAW resonators to replace the external quartz crystal and the external band select filter. It has been fabricated in a 130 nm CMOS process and has a power consumption of 5 mA. To derive the specifications for the transceiver the requirements of a TPMS have been taken into consideration.Der Einsatz von BAW-Resonatoren fü r drahtlose Sensornetzwerke im automotiven Bereich.Der folgende Artikel stellt einen 2,1-GHz-Transceiver vor, der anstelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Small sized shock-resistant BAW resonators are utilized for several purposes: carrier generation in transmit mode, local oscillator (LO) generation in receive mode, clock generation for the digital signal processing unit and lC's CPU, and as band select filters in the receive chain Flatscher et al 2008). In contrast to state of the art transceivers, the BAW based oscillators are directly resonating at the carrier frequency of 2.1 GHz, and therefore no phase locked loop is required.…”
Section: Bulk Acoustic Wave (Baw) Based Transceivermentioning
confidence: 99%
See 3 more Smart Citations
“…Small sized shock-resistant BAW resonators are utilized for several purposes: carrier generation in transmit mode, local oscillator (LO) generation in receive mode, clock generation for the digital signal processing unit and lC's CPU, and as band select filters in the receive chain Flatscher et al 2008). In contrast to state of the art transceivers, the BAW based oscillators are directly resonating at the carrier frequency of 2.1 GHz, and therefore no phase locked loop is required.…”
Section: Bulk Acoustic Wave (Baw) Based Transceivermentioning
confidence: 99%
“…Furthermore the electrical behavior of the BAW resonator can be modeled conveniently, as presented in (Flatscher et al 2008), where the BAW is shown to have an impedance of 2 kX at the parallel resonance frequency of 2.1 GHz. This property of the BAW turned out to be a major design issue, when connected to the transceiver die via TSVs, since this high impedance causes significant losses to the substrate.…”
Section: Bulk Acoustic Wave (Baw) Based Transceivermentioning
confidence: 99%
See 2 more Smart Citations
“…Additional benefits offered by a solidly mounted BAW resonator include extremely high mechanical robustness, higher quality factor (Q) than surface acoustic wave (SAW) devices or on-chip LC, small size, and lower temperature dependency as well as 10 times higher ESD robustness than SAW (5)(6) (7). Furthermore, the electrical behavior of the BAW resonator can be modeled conveniently, as presented in (8), where the BAW is shown to have an impedance of 2 kȍ if oscillating at 2.1 GHz. This property of the BAW turned out to be a major design issue, when connected to the transceiver die via TSVs, since such high impedance causes significant losses to the substrate.…”
Section: The Wireless Sensor Nodementioning
confidence: 99%